Razzle Dazzle: En camoufleret avantgarde - Kristensen, Jens Tang (Passage - Tidsskrift for litteratur og kritik, 2018)
Jens Tang Kristensen: “Razzle Dazzle. The Camouflaged Avant-Garde” This article demonstrates that Razzle Dazzle, a type of camouflage applied to war and merchant ships in the early twentieth century, can be seen as a complex form of visual expression that emerged in close dialogue with several of the avant-garde movements which appeared in the same period. In a sense Razzle Dazzle can thus further be seen as a mode by which the avant-garde was inadvertently integrated into the military sector, which certain avant-garde groups, namely the Futurists, idealized.